Single-Operator Peroral Cholangioscopy for Extraction of Cystic Duct Stones in Postcholecystectomy Mirizzi Syndrome - Jason Deforest Jones; Rishi Pawa (Case Reports in Gastrointestinal Medicine)
Mirizzi syndrome is an exceptionally rare diagnosis with an annual incidence of less than 1% in developed countries. In this disease process, stone burden in the cystic duct or gallbladder neck leads to common hepatic duct obstruction, either by mechanical compression or secondary inflammation. Mirizzi syndrome is classified into one of four types based on the presence and severity of cholecystobiliary fistulization. Treatment is primarily surgical in nature and largely dictated by the type of Mirizzi syndrome encountered. It is typically diagnosed in the preoperative or operative setting of cholecystectomy; however, there have been rare occurrences of postcholecystectomy diagnosis. Factors thought to predispose to postcholecystectomy disease include low insertion of the cystic duct and long remnant duct length. Few case reports exist describing this phenomenon and its management, which is made exceptionally difficult due to the presence of inflammation and surgical adhesion. We present the case of a young female with postcholecystectomy Mirizzi syndrome who underwent successful endoscopic management using peroral cholangioscopy and electrohydraulic lithotripsy. We also provide a brief overview of both Mirizzi syndrome and peroral cholangioscopy.